Pembedahan Transoral Endoscopic Thyroidectomy Vestibular (TOETVA) - Nur Qodir (Conferences of Medical Sciences Dies Natalis, 2019)
The thyroid is a butterfly-shaped gland located at the base of the neck, consisting of two lobes that sit on either side of the trachea. It releases hormones necessary for many of the body’s vital functions, including metabolism, heart rate, body temperature, and growth and development. The term thyroid nodule refers to an abnormal growth of thyroid cells that forms a lump within the thyroid gland. More than 95% of all thyroid nodules are benign. Some thyroid nodules are actually cysts, which are filled with fluid rather than thyroid tissue.Thyroid nodules are three times more common in women than in men. Most women will develop a thyroid nodule by the time they are 50 years old. The incidence of thyroid nodules increases with age. 50% of 50-year-old women will have at least one thyroid nodule. 60% of 60-year-old women will have at least one thyroid nodule. 70% of 70-year-old women will have at least one thyroid nodule.Requisite to adopting any new surgical technique is scrutiny and analysis to confirm that the procedure is feasible and safe with the ultimate comparison to the gold standard of open transcervical thyroidectomy. However, this approach leaves an unavoidably visible neck scar. Many modified techniques have been developed to reduce the size of the neck scar, including minimally-invasive open thyroid surgery and video-assisted thyroidectomy (MIVAT). Many of the alternative approaches for pure endoscopic thyroidectomy move the wounds to other parts of the body Such an approach is unparalleled compared to other remote-access approaches such as the axilla, breast, or post-auricular area, but cutaneous scars are still apparent and these approaches require a large amount of flap dissection.Natural Orifice Transluminal Endoscopic Surgery (NOTES) for thyroidectomy was developed. This surgical technique completely avoids visible cutaneous scarring with an approach through the oral cavity. Two techniques have been described, including 1) a sublingual approach, which causes severe tissue damage with a high complication rate and 2) an transoral endoscopic thyroidectomy vestibular approach (TOETVA).A major advantage of TOETVA is the midline approach to the central neck, which allows access for a total thyroidectomy and central neck dissection.